PENERAPAN SISTEM PENGENDALIAN INTERN PEMERINTAH (SPIP) PADA KPU PROVINSI JAMBI - Prenadia Paramita; Roni Ekha Putera; Aidinil Zetra (Jurusan Ilmu Komunikasi Universitas Andalas, 2021)
Accountability is one element in the realization of an election with integrity. The accountability aspect is one of the ways to legitimize election organizers and prevent potential fraud in the election budget, so internal and external monitoring is needed. The application of the Government Internal Control System (SPIP) is a form of internal control that is closely related to the quality of financial administration of a government agency. PP Number 60 of 2008 which regulates the application of SPIP in Indonesia adopts the COSO internal control theory which states that internal control consists of 5 elements, namely the control environment, risk assessment, control activities, information and communication, and monitoring. By using a qualitative method through a case study approach, this study intends to analyze the implementation of the Government's Internal Control System at the KPU Jambi Province. From the results of the study, it was concluded that the implementation of SPIP at KPU Jambi Province was sufficient, especially in the elements of information and communication. Meanwhile, other elements of SPIP, namely the control environment, risk assessment, control activities, and monitoring still have weaknesses.